C-Terminally modified peptides via cleavage of the HMBA linker by O-, N- or S-nucleophiles. Issue 12 (29th February 2016) - Hansen, J.; Diness, F.; Meldal, M.
Abstract : A direct and convenient method for the release of protected peptides with C-terminal modification from the HMBA linker by nucleophilic cleavage with amines, alcoholates or thiolates. Abstract : A large variety of C-terminally modified peptides was obtained by nucleophilic cleavage of the ester bond in solid phase linked peptide esters of 4-hydroxymethyl benzamide (HMBA). The developed methods provided peptides, C-terminally functionalized as esters, amides and thioesters, with high purity directly from the resin in a single reaction step. A comprehensive screening of the reaction conditions and scope for nucleophilic cleavage of peptides from the HMBA linker was performed.